Intravascular inflammation - from Mechnikov’s idea to the present day - Peremot, S; Smilianska, M; Kashpur, N (Annals of Mechnikov’s Institute, 2020)
For more than a century, the name of I.I. Mechnikov has been shining in the constellation of the names of outstanding scientists, whose works laid the foundations for the formation of a scientific worldview of all living things: from a small microorganism to a person. He is considered the founder of comparative pathology and the theory of immunity, a scientist who stood at the origins of evolutionary embryology, microbiology and immunology. He formulated the general theory of inflammation as a protective reaction of the body in the fight against infection. The enormous significance of Mechnikov’s scientific heritage is based primarily on deep materialistic and evolutionary principles, a consistent conductor and passionate champion of which he has been throughout his life. Biology and medicine owe the scientist not only many brilliant discoveries and firmly facts, but also significant broad generalizations laid the foundation for a number of the most progressive areas of modern biology and medicine. These include the concept of «intravascular inflammation». Using this definition, Mechnikov argued about the possibility of phagocytosis of bacteria by circulating leukocytes. The main idea formulated by him is consonant with the modern concept that, according to I. I. Mechnikov, «harmful factors», getting into the blood, excite the reaction of phagocytes, the main effector mechanism of inflammation. What happens with the classic inflammatory response is «extravasal», thanks to the emigration of cells from the bloodstream. He speaks of «intravascular inflammation» only once, without focusing attention, however, he testifies to the correspondence with the main idea. The scientific thought formulated by Mechnikov, rethought and reinforced by the results of studies of his followers, found its continuation in the modern concept of intravascular inflammation. In general, it can be argued that Mechnikov made a scientific feat, the scale of which becomes all the more obvious the farther he is from us in the historical interval and there is no doubt that the ideas and methodology of our great countryman will be key in the 21st century for new fundamental discoveries in the field of natural sciences. DOI: 10.5281/zenodo.3885238